The Influence of Corporate Governance Implementation toward Bank Performance (Empirical Study on Banks Listed in Indonesia Stock Exchange) - Heriyanni Mashitoh; . Irma (UBL, 2013)
This study is aimed to investigate the effect of corporate governance indicators such as the board of directors, audit committee and audit quality to the bank performance which is proxied by Camel ratio such as CAR, NPL, LDR, ROA, BOPO and ROE. The samples were 30 listed banks in the Indonesia Stock Exchange. Structural Equation Modelling (SEM) was used to test the influence of corporate governance indicators to the bank performance. The test results proved that the board of commissioners had a significant positive correlation to the bank performance. It means the higher the commissionersâ supervision the better the performance of the bank. Similarly, the audit quality also has a significant positive correlation to the bank performanc which means the higher the audit quality, the better the performance of the bank. It has also been revealed that the audit committee, although positively related to bank performance but it is not significantly proved. The results of this study support the previous studies, the research of Nasution and Setiawan (2007), Abeysekera (2008), and Xie et. al. (2003).